Optimalisasi Kriteria Green Building untuk Gedung Fakultas Teknik Sipil dan Perencanaan ITN Malang dalam Mendukung Pembangunan Berkelanjutan - Taufiq, Elvina Sari; Abidin, Afri Ahyarki; Olivia Catrina Dora; Ihsan Dwi (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2024)
Karang Besuki Village, particularly the Jalan Raya Candi II corridor, is recognized as a promising hub for the sanitary industry. However, technological advancements and social changes present challenges in maintaining the area’s identity. This study aims to analyze the impact of the built environment on the identity of the sanitary industry area using a descriptive qualitative approach, while also providing community service-based strategic recommendations for preserving the area’s identity. The analysis focuses on building functions, visual elements, and the built environment's characteristics that support the area's existence as a sanitary industry center in Malang City. Additionally, the study examines changes in residential building functions within the corridor to identify factors influencing the area's visual image. Through a community service-based approach, this research is expected to strengthen collaboration between local communities, government, and stakeholders